1992
DOI: 10.1161/01.atv.12.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary monounsaturated and polyunsaturated fatty acids on the susceptibility of plasma low density lipoproteins to oxidative modification.

Abstract: Oxidized low density lipoproteins (LDLs) are thought to play an important role in atherogenesis. Nutritional and biochemical studies suggest that diet can modulate the susceptibility of plasma LDL to undergo oxidative degradation by affecting the concentration of polyunsaturated fatty acids and antioxidants in the lipoprotein particle. In the present study 11 healthy male volunteers underwent two diet phases. In one phase the diet was enriched in oleic acid (mono), while in the other it was high in linoleic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
99
1
5

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(116 citation statements)
references
References 26 publications
11
99
1
5
Order By: Relevance
“…Reaven et al [34] showed that the extent of LDL oxidation is strongly influenced by the LDL linoleic acid content. More recently, dietary studies have shown that the enrichment of LDL linoteic acid by dietary manipulation resulted in an increase in oxidisability [35,36]; our results confirm those findings. The diabetic subjects in this study had a raised percentage of linoleic acid in their cholesteryl ester and this positively correlated with oxidisability.…”
Section: Discussionsupporting
confidence: 91%
“…Reaven et al [34] showed that the extent of LDL oxidation is strongly influenced by the LDL linoleic acid content. More recently, dietary studies have shown that the enrichment of LDL linoteic acid by dietary manipulation resulted in an increase in oxidisability [35,36]; our results confirm those findings. The diabetic subjects in this study had a raised percentage of linoleic acid in their cholesteryl ester and this positively correlated with oxidisability.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that diets high in linoleic acid result in LDL that are more susceptible to in vitro oxidation than those high in oleic acid (Bonanome et al, 1992;Reaven et al, 1991). Therefore, we measured the susceptibility of LDL to copper-mediated oxidation in women fed on reference and walnut diets.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that a high-monounsaturated fat diet lowers the risk of coronary heart disease by producing LDL particles that are enriched in oleic acid at the expense of linoleic acid (C18:2n-6). Such a change in fatty acid composition renders LDL particles more resistant to oxidative modification (Reaven et al, 1991;Berry et al, 1992;Bonanome et al, 1992;Mata et al, 1997).…”
Section: Introductionmentioning
confidence: 99%